AN ANALYSIS OF GRAMMATICAL ERROR ON STUDENTS’ PERSONAL LETTER WRITING - Ikrima, Ima (Foremost Journal, 2020)
ABSTRACTThe objectives of this research are to know the types, the frequencies, the factors of an error analysis and to find out how to improve the grammatical errors made by students on the use of article, preposition, and pronoun in writing personal letter on the eleventh grade of students of SMAN 3 Kabupaten Tangerang. The research used descriptive analysis method. There were 424 students as the population, and sample of this research consisted 70 students which are divided into two classes, and chosen by using random sampling. The writer found that the most common errors made by the students is use of preposition with the total number 30 errors or 54.54%. The second rate is the use of article with the total number 22 errors or 40.00%. The last is the use of pronoun with the total number 3 errors or 5.54%. The conclusion of this study is the students still made errors on the use of grammar in writing personal personal letter including the use of article, preposition, and pronoun. Keywords: error analysis, grammatical error, personal letter, writing skill